A new synthesis of limonene copolymer: experimental and theoretical analysis - Cankaya, Nevin; Tanis, Emine; Gulbas, H. Elmali; Bulut, Niyazi (Springer, 2019)
A copolymer of limonene with 2-(4-methoxyphenylamino)-2-oxoethyl methacrylate (LIM-co-MPAEMA) which is thought to be a non-toxic and used generally as a dietary supplement was synthesized and characterized for the first time both experimentally and theoretically. The structure of synthesized limonene copolymer was chemically characterized by Fourier transform infrared and nuclear magnetic resonant (H-1 NMR) spectroscopic techniques and compared with the theoretical calculated results. Charge transfer that is important in the formation of chemically bonded adducts causing cancer is quantitatively calculated. It was found that this polymer can be used as a biomaterial.
Keywords: 2-(4-Methoxyphenylamino)-2-oxoethyl methacrylate (MPAEMA); Limonene; LIM-co-MPAEMA; Density functional theory (DFT)